Teachers’ Test Construction Skills in Senior High Schools in Ghana: Document Analysis - Frank Quansah; Francis Ankomah; İsaac Amoako (International Journal of Assessment Tools in Education)
Assessment, specifically test construction,forms a critical part of the teaching and learning process. This aspect ofteachers’ responsibility has been questioned by several authorities incontemporary times. The study explored the test construction skills of SeniorHigh Schools (SHS) teachers in the Cape Coast Metropolis. Using a qualitativedocument analysis, samples of End-of-Term Examination papers in IntegratedScience, Core Mathematics and Social Studies in three selected SHS in the CapeCoast Metropolis were randomly (Lottery method) selected. The assessment taskson the sampled instruments were critically examined by experts in the area ofEducational Measurement and Evaluation. The results revealed that the teachershave limited skills in the construction of end-of-term examination. This wasevident as issues were found with the content representativeness and relevanceof the test, reliability, and fairness of the assessment tasks which wereevaluated. It was recommended that head teachers should take up the challengeof inviting resource persons from recognised academic institutions to organiseworkshops for teachers on a regular basis to sharpen their skills on effectivetest construction practices.